Il ruolo dei neuroni specchio nell’empatia - Francesco Rovatti (Formazione & insegnamento, 2020)
The article will focus on revising based on recent studies regarding the synergies which lie in between educational psychology and cognitive neuro sciences; furthermore in the following paper a significant emphasis will be attributed to the discovery of the mirror neurons as the basis of empathy and to the relative implications concerning the educational, social and clinical fields.